Artificial Intelligence (AI) and Jean-Paul Sartre’s Existentialism: The Link - Ubah, Ugonna Ezinne (WritingThreeSixty: Journal or Research and Creative Text, 2024)
Background: The supremacy of man in the idea of existentialism positions him as the core component of nature. As the being that proposed the idea of Artificial Intelligence (AI), man is at the center of everything. The ideology of Existentialism, which champions the liberty of man to actualize his own ideas and create his essence in the world, does not believe in God. One aspect of this essence is the manifestation of AI, a creation that has made man more resourceful in his society. This paper delves into the significance of man’s creation of AI and its profound link with the philosophy of Existentialism. Drawing from a broader philosophical context, this study explores the influence of Jean-Paul Sartre’s existentialist works on Artificial Intelligence (AI) and how the latter has reflected on the nature of man. In conclusion, this paper will elaborate more on the significance of Artificial Intelligence (AI) in the nature of man, emphasizing man’s role in its creation.